Alterations in the Gut Microbiota of Tibetan Patients With Echinococcosis - Cao, Deping; Pang, Mingquan; Wu, Defang; Chen, Gen; Peng, Xiaohong; Xu, Kai; Fan, Haining (Frontiers in Microbiology, 2022)
Echinococcosis is a zoonotic parasitic disease caused by the metacestodes of Echinococcus multilocularis and Echinococcus granulosus. In order to analyze the gut fecal microbiome composition of patients with echinococcosis, we analyzed the fecal samples of 7 patients with alveolar echinococcosis, 6 patients with cystic echinococcosis, and 13 healthy individuals from the Qinghai-Tibetan Plateau, China. Using next-generation metagenomic sequencing, we identified fecal bacteria in the patients with echinococcosis. Compared to patients with cystic echinococcosis, the dominant bacteria in the gut of healthy donors were Actinobacteria at the phylum and class levels. Phascolarctobacterium succinatutens is a significant species in the intestines of healthy individuals. The dominant bacteria in the intestines of patients with cystic echinococcosis were Bacteroides vulgatus, Bacteroides dorei, and Streptococcus vestibularis. Veillonella atypica, Streptococcus salivarius, and Alistipes finegoldii were abundant in the feces of patients with alveolar echinococcosis. Bacteroides caccae, Alistipes onderdonkii, and A. finegoldii were present in the feces of patients with alveolar echinococcosis, and were almost absent in those of patients with cystic echinococcosis and healthy donors. Our results suggest that (1) P. succinatutens is a highly abundant species in the intestines of healthy individuals, and (2) A. finegoldii and B. caccae may be used as potential biomarkers for alveolar and cystic echinococcosis, as well as for healthy individuals. In addition, the results of this study enrich our understanding of the gut microbiome composition of echinococcosis in the Qinghai-Tibetan Plateau.